Augmenting the distillate yield of cords pyramid distiller with baffles within compartments. (1st July 2022) - Alawee, Wissam H.; Abdullah, A.S.; Mohammed, Suha A.; Dhahad, Hayder A.; Omara, Z.M.; Essa, F.A.
Abstract: Although solar still is an alternative solution to the shortage of potable water (for some applications), they suffer from low output yield. This paper aims at improving the performance of pyramid distiller (PSD) via installing a parallel liner plate at 3 cm above the base liner. This plate had 35 cracks on its surface. The plate upper surface was covered by wick. Also, 35 dangled wick cords were fixed in the cracks of the plate. In addition, six baffles were fixed in the modified cords pyramid solar distiller (CPSD) to reduce the amount of water in the basin and thus raise its water temperature. Besides, different wick types (jute cloth and cotton wick) were investigated. Additionally, three types of nanoparticles were investigated: Ag, CuO, and TiO2 . The nanoparticles were mixed with black paint, and the mixture was used to paint the walls of CPSD. Economic and environmental analyses were conducted to confirm the reliability of CPSD results. Results revealed that CPSD with baffles and Ag improved the productivity by 176% over PSD, and the thermal efficiency reached 60.4%. The environmental parameter of CPSD with baffles and Ag was 28.71 tons CO2 per year.